External dose evaluation based on detailed air dose rate measurements in living environments - Sato, Tetsuro; Andoh, Masaki; Sato, Masako; Saito, Kimiaki (Journal of environmental radioactivity, 2019)
A method was devised to estimate the realistic external doses of residents expected to return to their homes after evacuation orders are lifted. For 196 residents expected to return to six towns and villages, surveys were administered in FY 2014–2016. After interviewing residents about their expected life patterns after their return, detailed air dose rate measurements were taken along their reported personal routes representing patterns of movement in their daily life. The maximum and average annual additional external effective dose were estimated at 4.9 mSv and 0.86 mSv, respectively. Although the mean values and dispersion of external effective doses differed depending on the level of evacuation, for 93.3% of all residents, the estimated annual additional external effective doses were less than 2 mSv. Measuring air dose rates inside houses was found to be important to obtain a realistic evaluation of the external exposure dose because our research revealed that the average time spent indoors was 87% of the total living time. Moreover, the average exposure dose at home accounted for 66.8% of the annual exposure dose. •A new method to estimate realistic doses of returning residents based on detailed air dose rate measurements was devised.•The correlation between indoor and outdoor air dose rate was investigated.•The proportion of exposure dose at home to total exposure dose was investigated.